2021
DOI: 10.1051/ro/2021030
|View full text |Cite
|
Sign up to set email alerts
|

A note on parallel-machine scheduling with controllable processing times and job-dependent learning effects

Abstract: This note studies a unrelated parallel-machine scheduling problem with controllable processing times and job-dependent learning effects, where the objective function is to minimize the weighted sum of total completion time, total load, and total  compression cost. We show that the problem can be solved in $O(n^{m+2})$ time, where $m$ and $n$ are the numbers of machines and jobs. We also show how to apply the technique to several single-machine scheduling problems with total criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In future research, we can extend it to multi-machine problems such as parallel machines or flow shop settings. It is also interesting to extend the model to the single-machine group scheduling problem with general shortened job processing times, due-date assignment (see [29]) or positional-dependent learning effects (see [2,4,13]).…”
Section: Discussionmentioning
confidence: 99%
“…In future research, we can extend it to multi-machine problems such as parallel machines or flow shop settings. It is also interesting to extend the model to the single-machine group scheduling problem with general shortened job processing times, due-date assignment (see [29]) or positional-dependent learning effects (see [2,4,13]).…”
Section: Discussionmentioning
confidence: 99%
“…We will show that C j (σ) ≤ C i (σ ′ ). Taking the difference between (20) and (22), it is obtained that…”
Section: The Nondecreasing Function F(x Y) On Xmentioning
confidence: 99%
“…e distinctive proof technique is developed based on the adding-term operation, the subtracting-term operation, and the Lagrange mean value theorem. Lin [20] studied job-dependent learning effect and controllable processing time on the unrelated parallel machine. e three objective functions are considered, including the weighted sum of total completion time, total load, and total compression cost.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed an integer non-linear programming model and a dynamic programming model, which can be executed in pseudo-polynomial time. While Lin [13] addressed the parallel-machine scheduling with controllable processing times and job-dependent learning effects, the objective function is to minimize the weighted sum of total completion time, total compression cost, and total load. They showed that the problem can be solved in O(n m+2 ) time, where n (resp.…”
Section: Introductionmentioning
confidence: 99%